Synopsis of the genus Empicoris (Hemiptera: Heteroptera: Reduviidae) in Chile - Melo, María Cecilia (2011)
The species of Empicoris Wolff, 1811 recorded from Chile are listed, and an identification key for all four species is provided. New distributional records from Chile are added: E. errabundus (Say, 1832) and E. vagabundus (Linnaeus, 1758), the last species is recorded for the first time from the Neotropical Region.